1994
DOI: 10.1002/ajmg.1320510426
|View full text |Cite
|
Sign up to set email alerts
|

Fragile X induction systems in CVS cultures: Effect on cytogenetic, PCR, and genomic southern blot DNA analyses of the FMR‐1 gene

Abstract: Low fragile X frequencies have been commonly observed in chorionic villus sample (CVS) cultures, compared to subsequent analysis in whole blood or products of conception (POC). To investigate possible mechanisms for this effect, CVS cultures from a previously identified fragile X positive male, were restudied and compared to subsequent POC cultures from lung, muscle, skin, and thymus. Cultures were exposed, for the last 24 hours before harvesting, to FUdR, excess thymidine, and a combination of both. For CVS, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
1997
1997

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…CVS has the advantage over amniocentesis of an earlier and speedier diagnosis but there are technical problems. Several studies have reported abnormal methylation patterns in chorionic villi whereby FMs genes are hypomethylated relative to foetal tissue (Sutherland et al, 1991a;Iida et al, 1994;Castellvi-Bel et al, 1995;Yamauchi et al, 1993;Jenkins et al, 1994b;Suther-land et al, 1991b). Consequently, lyonisation of the inactive X is not observed and foetal sex determination requires additional PCR amplification of Xand Y-specific DNA (Devys et al, 1992).…”
Section: Prenatal Diagnosismentioning
confidence: 99%
“…CVS has the advantage over amniocentesis of an earlier and speedier diagnosis but there are technical problems. Several studies have reported abnormal methylation patterns in chorionic villi whereby FMs genes are hypomethylated relative to foetal tissue (Sutherland et al, 1991a;Iida et al, 1994;Castellvi-Bel et al, 1995;Yamauchi et al, 1993;Jenkins et al, 1994b;Suther-land et al, 1991b). Consequently, lyonisation of the inactive X is not observed and foetal sex determination requires additional PCR amplification of Xand Y-specific DNA (Devys et al, 1992).…”
Section: Prenatal Diagnosismentioning
confidence: 99%